Are third states pulling the strings? The impact of domestic policy change on EU-third state cooperation. Issue 7 (2nd October 2020) - Guérin, Nina; Rittberger, Berthold
ABSTRACT: Since the launch of the European Neighbourhood Policy (ENP) in 2004, scholars have extensively analysed whether the EU's external governance strategy is effective. In this paper, we propose a change in perspective and argue that domestic policy change in third countries is not merely a possible outcome of the EU-third state cooperation, but also a condition for the design of cooperation between the EU and third states in the first place. ENP states with a track record of domestic policy reforms are more likely to agree on a comprehensive reform agenda with the EU than states with no prior domestic reform activities. This implies that third states are 'pulling the strings', since their willingness and capacity for reform is the crucial determinant of close cooperation with the EU. We probe our argument in the field of asylum policy across all 16 ENP states and proceed with a within-case analysis of asylum policy reform in Moldova.